2012
DOI: 10.1080/02673843.2012.719828
|View full text |Cite
|
Sign up to set email alerts
|

Thinking patterns, victimisation and bullying among adolescents in a South Australian metropolitan secondary school

Abstract: Responding to staff concerns about anti-social behaviour among students (n ¼ 311, 50.5% boys, age range 13 -16 years) at a low socio-economic Adelaide metropolitan school, we investigated victimisation and bullying and associated patterns of thinking. Two instruments were administered: the How I Think Questionnaire, which measures self-serving cognitive distortions; and the Bullying Experiences Questionnaire, which requires students to rate victimisation and bullying. The study revealed that: levels of distort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 34 publications
3
26
0
3
Order By: Relevance
“…Despite an increasing number of researchers [18,19,51] having found a link between self-serving CDs and externalizing behaviors, only one study [22], carried out with Australian adolescents, has examined the association between CDs and bullying at school. The authors found that bullies and bully-victims showed a higher tendency than victims and not-involved persons in assuming the worst, exhibiting minimizing-mislabeling and self-centered CDs, whereas only bullies were higher in blaming others.…”
Section: Self-serving Cognitive Distortions and School Bullying Perpementioning
confidence: 99%
See 2 more Smart Citations
“…Despite an increasing number of researchers [18,19,51] having found a link between self-serving CDs and externalizing behaviors, only one study [22], carried out with Australian adolescents, has examined the association between CDs and bullying at school. The authors found that bullies and bully-victims showed a higher tendency than victims and not-involved persons in assuming the worst, exhibiting minimizing-mislabeling and self-centered CDs, whereas only bullies were higher in blaming others.…”
Section: Self-serving Cognitive Distortions and School Bullying Perpementioning
confidence: 99%
“…Given that age-and gender-based differences have been observed in violence exposure, cognitive distortions and bullying behavior in previous research, we controlled the results for school grade and gender. Overall, prior studies have consistently found that males and older children are at greater risk for community violence exposure (e.g., [70]) and bullying perpetration (e.g., [71]); and males typically also self-report more cognitive distortions than females [22,72]. Parental socioeconomic status (SES) was also used as control variable, given its potential confounding effect on violence exposure [38] and bullying perpetration [73].…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Distorted cognitions, in turn, have been emphasized as a risk factor for social and behavioral maladjustment, such as bullying perpetration and victimization (Cook et al, ; Marsh, Parada, Yeung, & Healey, ; Owens, Skrzypiec, & Wadham, ). Beck () proposed that distorted thoughts organize according to distinct areas of cognitive content such as threat and loss/failure, others and self.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive distorsions relevant for bullying involvement are characterized by a diversity of themes or contents, concerning both self and others (Cook et al, ). For instance, bullies and bullies‐victims endorse higher levels of self‐serving cognitive distortions than uninvolved peers, whereas negative self‐views have been shown to be a risk factor for peer victimization (Egan & Perry, ; Owens et al, ). Furthermore, in a longitudinal study, Marsh et al () have documented the role of negative self‐concept and evaluations of oneself as a worthless person in predicting involvement in both bullying perpetration and victimization.…”
Section: Introductionmentioning
confidence: 99%